Data from a Large Hemodialysis Center form an Industrial City: Demographics, Etiology and Hepatitis Status - Shahbaz, Muhammad (Pakistan Journal of Kidney Diseases, 2021)
Chronic kidney disease posts a huge burden on health care cost and its associated morbidity and mortality. Knowledge of the disease burden is only possible by documentation of patient data. We here present our data for our dialysis patients from one of the largest industrial city Faisalabad, Pakistan. It is interesting to note that almost half of our patients were hepatitis C virus positive. We are hopeful that such data will be useful for the policy makers and health care providers to plan for future health care needs of maintenance hemodialysis patients.